Sustaining distributive leadership in learning and teaching : cascade and perpetual effectiveness of the faculty scholar model. - Smigiel, Heather; Govin, Kay; Deller-Evans, Kate; Pannan, Linda; Szorenyi-Reischl, Nick; Donnan, Peter (Australian Learning and Teaching Council, 2011)
This was a build-on project to further investigate the findings in The GREEN Report. One of the key aims was to further develop the distributive leadership capacity building framework for teaching and learning. This aim was partially achievable because the two project leaders had participated in the first distributive leadership project and its evaluation, and had first-hand experience of the strengths and weaknesses of the model. Another key aim was the evaluation of the outcomes for leadership scholars from 2007-2009 in relation to leadership capacity building. Interestingly, preparation, planning and participation in the roundtable were viewed by the former scholars as being a crucial domain that had a very significant impact on their development of leadership skills. Unfortunately, this element is the most difficult to replicate if a university wishes to implement the faculty scholar model on its own. Of the six universities involved in the project, four have now introduced faculty scholars and funded the project themselves. The four institutions have used the model and the domains, but have not been able to include the national networking and the roundtable. --ALTC website